Bird Diversity and its Potential for Tourism Activities In Mandeh Mangrove Forest, West Sumatra, Indonesia - Novita, Aulya; Mukhta, Erizal; Novarino, Wilson (Jurnal Biologi Tropis, 2025)
Avitourism is a form of tourism that focuses on bird watching in their natural habitat. The existence of mangrove forests is very important in an area because it is a habitat for various types of wildlife, especially birds. This study aims to analyze bird diversity and its potential in tourism activities in the Mandeh mangrove ecosystem area. This research was conducted from February to April 2024. The method used was the point count method. Data collection of bird species and numbers was carried out at 15 observation points. The distance of each observation point is 150 meters with an observation radius of 50 meters. Data collection was carried out for 10 minutes at each point. Observations were conducted for four days, and continued with bird species identification. Data analysis used was Shannon Wiener diversity index, evenness index and richness index. The results found 32 bird species from 18 families. Dominated by the Apodidae and Estrildidae families. The diversity index value is 2.17 with moderate index criteria. evenness index 0.63 which is included in the uneven category and a wealth index of 4.96 with a high wealth category. Birds that have ecotourism attractions found are 1 type of endemic bird, not found raptor birds, 2 types of birds listed on the IUCN, 7 types of melodious sound birds and 16 types of beautiful feathers, so that the Mandeh mangrove ecosystem area has potential.